2014
DOI: 10.5325/jgeneeduc.63.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Test of Scientific Literacy Skills in the Assessment of a General Education Natural Science Program

Abstract: The peer-reviewed and psychometrically validated Test of Scientific Literacy Skills developed by Gormally et al. was used to assess the strengths and weaknesses of a general education natural science program. By comparing the scores of students who had already taken at least one course in this area with the scores of those who had not, and by relating scores to students' perceptions of learning about science, a richer understanding of our program has emerged. The ability to focus on particular skill sets and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Of the ten surveys that applied the TOSLS and its adapted versions, mean scores higher than 50% were found in the studies by Čipková et al (2020), Shaffer et al (2019), andWaldo (2014), and mean scores below this value were noted by Gomes and Almeida (2016), Kola et al (2020), Santiago et al (2020), and Utami and Hariastuti (2019). Gormally et al (2012) observed significant gains in science literacy skills on the post-test.…”
Section: Study Results: Performance In Scientific Literacy Assessmentmentioning
confidence: 90%
See 3 more Smart Citations
“…Of the ten surveys that applied the TOSLS and its adapted versions, mean scores higher than 50% were found in the studies by Čipková et al (2020), Shaffer et al (2019), andWaldo (2014), and mean scores below this value were noted by Gomes and Almeida (2016), Kola et al (2020), Santiago et al (2020), and Utami and Hariastuti (2019). Gormally et al (2012) observed significant gains in science literacy skills on the post-test.…”
Section: Study Results: Performance In Scientific Literacy Assessmentmentioning
confidence: 90%
“…As for the TOSLS, Gormally et al (2012), Santiago et al (2020) and Souza (2019) reported the hit frequencies by skill, Shaffer et al (2019) presented them by skill categories and Cartwright et al (2020), Čipková et al (2020), Gomes and Almeida (2016), Kola et al ( 2020), Utami and Hariastuti (2019) and Waldo (2014) reported the hit frequencies of the instrument as a whole.…”
Section: Ways Of Presenting and Analyzing The Results Of Scientific L...mentioning
confidence: 99%
See 2 more Smart Citations
“…Dentre os estudos que utilizaram o TOSLS, não houve predominância positiva ou negativa de nenhuma das habilidades. No caso das melhores habilidades, as pesquisas de Santiago et al (2020) e de Čipková et al (2020) identificaram a habilidade de avaliar os usos e os usos indevidos das informações científicas; Souza (2019) constatou a habilidade de identificar um argumento científico válido; Utami e Hariastuti (2019) verificaram a habilidade de resolver problemas usando habilidades quantitativas, incluindo análises estatísticas básicas; Waldo (2014) identificou as habilidades da categoria 1, relacionadas com o reconhecimento e com a análise do uso de métodos de investigação que levam ao conhecimento científico; e Gomes e Almeida (2016) observaram as habilidades de identificar um argumento científico válido, de avaliar os usos e os usos indevidos das informações científicas, de compreender os elementos de um projeto de pesquisa e como estes impactam nas descobertas/conclusões científicas, de criar um gráfico apropriado a partir dos dados e de justificar as inferências, previsões e conclusões com base em dados quantitativos.…”
Section: Resultados Dos Estudos: Desempenho Nas Dimensões Da Literaci...unclassified